SEX DETERMINATION FROM FINGERPRINTS AMONG SOUTH INDIAN POPULATION - Renjith, Remya; Kumar, Ashwini (Journal of Forensic Medicine and Toxicology, 2021)
Person identification has always been an important aspect in every phase of investigation. The stature, sex, age and race are the basic features that we look for. Fingerprints were always a reliable source for individual identification. It is unique, universal, non-replicable form of evidence which differ from person to person and even within finger